The Comparıson Of The Effects Of R.S.S.D. And Modıfıed Pendulum Applıances On Molar Dıstauzatıon - Ümit Gürton; Orhan Meral; Hüseyin Ölmez; Osman Bengi; Deniz Sağdıç (Galenos Yayinevi, 2000)
The most common problems of the intra-oral molar distalization techniques are anchorage loss and hygcnic problems. The aim of our study is to use our original R.S.S.D. (Removable Segmental Sliding Distalizer) Appliance and Modified Pendulum Appliance in molar distalization and compare their effects on dentofacial structures. Our study was carried on 40 lateral cephalograms obtained from 20 individuals, in the beginning and at the end of the distalization period. Working group consists of 8 girls and 12 boys who have skeletal Class I, dental Class II malocclusion and the mean age of the group is 11 years and 6 monihs. Distalization of the molars was continued in both groups until Class I molar relationship has been obtained. The cephalometric results were statistically evaluated by Wilcoxon and Mann Whitney U tests. Since R.S.S.D. Appliance is removable and Modified Pendulum Appliance is semi-removable no hygenic problems during the distalization period was observed and when the groups are compared R.S.S.D. Appliance was seen to be more succesfull in anchorage loss.